2019
DOI: 10.1007/s00442-019-04524-8
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for an association between Clock gene allelic variation and migration timing in a long-distance migratory shorebird (Limosa lapponica baueri)

Abstract: No evidence for an association between Clock gene allelic variation and migration timing in a long-distance migratory shorebird (Limosa lapponica baueri). Oecologia, 191(4), 843-859.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 102 publications
(147 reference statements)
0
10
2
Order By: Relevance
“…*, P < 0.10; **, P < 0.05; ***, P < 0.02. Caprioli et al, 2012;Kuhn et al, 2013) whilst others found no evidence for an association (Peterson et al, 2013;Contina et al, 2018;Parody-Merino et al, 2019). Additionally, several transcriptomic studies on related species have detected no differences in expression levels of key clock genes (Jones et al, 2008a;Franchini et al, 2017;Brown, 2019) used in candidate gene association studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…*, P < 0.10; **, P < 0.05; ***, P < 0.02. Caprioli et al, 2012;Kuhn et al, 2013) whilst others found no evidence for an association (Peterson et al, 2013;Contina et al, 2018;Parody-Merino et al, 2019). Additionally, several transcriptomic studies on related species have detected no differences in expression levels of key clock genes (Jones et al, 2008a;Franchini et al, 2017;Brown, 2019) used in candidate gene association studies.…”
Section: Discussionmentioning
confidence: 99%
“…The bar-tailed godwit subspecies Limosa lapponica baueri (Linnaeus) makes one of the most arduous annual journeys, breeding in Siberia and Alaska and overwintering in New Zealand. Parody-Merino et al (2019) reported a high degree of Clock variability, with three nearly equally distributed alleles Q 9 -Q 11 . Statistical analyses revealed no clear relationship between allele size and timing of migration, but a slight latitudinal cline was observed with longer alleles tending to be found in individuals that travel further north.…”
Section: Systematic Review Of Published Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in migratory birds focusing on CLOCK variation show mixed results. Longer allele lengths have been found to be positively correlated with migratory propensity (Peterson et al, 2013), and variation in the phenology of migratory species (Liedvogel et al, 2009; Caprioli et al, 2012; Bazzi et al, 2015), but in some cases allele lengths are negatively correlated with migration date (Ralston et al, 2019) or not correlated at all (Mueller et al, 2011; Contina et al, 2018; Parody-Merino et al, 2019). CLOCK plays a key role in regulating the circadian oscillator gene complex (Panda et al, 2002), and is associated with variation in the phenology of photoperiodic traits (e.g.…”
Section: Discussionmentioning
confidence: 99%